CRISPR: is the dream becoming a nightmare? A purpose of the political genetic experiment to protect two girls against aids virus - Adrianzén Avila, Jazmín (2019)
The present article can be a reflection from an ethical and legal perspective about CRISPR-CAS9, a promising and revolutionary technique that allows editing or correcting the specific and simple form of the genetic code. The economic accessibility, simplicity and the rapidity that characterize, have given rise to a new era in science, representing a great advance in the field of genetic publishing. However, there have been no limits, nor has it been published, but it has been included in the genetic edition in the germinal line, this technique has been applied in two fetuses, as the birthplace of two girls genetically engineered under this technique, in order to protect them from HIV virus, opening a great ethical, legal and social debate